Epigenome rewiring in human pluripotent stem cells. Issue 3 (March 2022) - Yan, Jielin; Huangfu, Danwei
Abstract : The epigenome plays a crucial role in modulating the activity of regulatory elements, thereby orchestrating diverse transcriptional programs during embryonic development. Human (h)PSC stepwise differentiation provides an excellent platform for capturing dynamic epigenomic events during lineage transition in human development. Here we discuss how recent technological advances, from epigenomic mapping to targeted perturbation, are providing a more comprehensive appreciation of remodeling of the chromatin landscape during human development with implications for aberrant rewiring in disease. We predict that the continuous innovation of hPSC differentiation methods, epigenome mapping, and CRISPR (clustered regularly interspaced short palindromic repeats) perturbation technologies will allow researchers to build toward not only a comprehensive understanding of the epigenomic mechanisms governing development, but also a highly flexible way to model diseases with opportunities for translation. Highlights: Rewiring of the epigenome contributes to human development. Stepwise human (h)PSC differentiation both facilitates and benefits from the understanding of epigenome rewiring. Epigenomic rewiring during hPSC differentiation occurs at both local and structural levels. The functional consequences of epigenomic rewiring on gene regulation can be interrogated with CRISPR (clustered regularly interspaced short palindromic repeats) technologies. Epigenomic information can predict disease causal risk variants and reveal aberrant epigenomic rewiring in disease.